PENINGKATAN HASIL BELAJAR PADA PEMBELAJARAN PKN MELALUI MODEL COOPERATIVE LEARNING TIPE SNOWBALL THROWING DI KELAS V SDN 11 SIKALANG - ZURNI ZURNI (STKIP Pesisir Selatan, 2020)
The achievement of learning objectives is determined by many factors including the factor of the teacher in implementing the teaching and learning process, because the teacher can directly influence, foster and improve students' intelligence and skills. To overcome the above problems and to achieve educational goals to the fullest, the role of the teacher is very important and it is hoped that the teacher has a good teaching method and is able to choose the right learning method and in accordance with the concepts of the subject to be delivered. One of the appropriate learning models in PKN learning is the Snowball Throwing learning model. The problems to be studied in this study are: Can the use of the Snowball Throwing learning model improve the science grade results of Class V students at SDN 11 Sikalang? The purpose of this action research is to improve the learning outcomes of PKN Class V SDN 11 Sikalang through the Snowball Throwing learning model. This study uses two rounds of classroom action research. Each round consists of four stages: planning, implementing, observing, reflecting. The targets of this study were students of Class V SDN 11 Sikalang. The data obtained are quantitative and qualitative data. From the results of the analysis of the PKN learning model has a positive impact in improving student learning outcomes characterized by increased student learning completeness in each cycle, namely the first cycle of the average learning outcomes of 73.53, and the second cycle of 83.53. The conclusion of this study is the Snowball Throwing learning model has a positive effect, which can improve student learning outcomes which are indicated by the average student answers stating that students are interested and interested in the Snowball Throwing learning model so that they become motivated to learn.